Analisis Sistem Pengolahan Data Berbasis Web pada Badan Pusat Statistik Kabupaten X - Fatimatuz Zahroh; Nur Rahmawati (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
The data processing system is a web-based system created by Central BPS to facilitate BPS District X employees to be able to help and speed up their work in processing data. This research aims to see how the web-based data processing system at BPS Kab. X. Data that has been collected in this study will be analyzed using the quantitative method in the validity and reliability test to find out whether the data is valid and reable to be continued in further processing. The results of this research are that all variables that have been tested produce valid and reliable data. The proposed improvement from the results obtained is to continue to improve the quality and improve the system better. Because the performance of a good data processing system will simplify the data processing process. So it will produce better, more accurate and relevant data